2014
DOI: 10.1055/s-0034-1383032
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy After a Laparoscopic Sacrohysteropexy: a Case Report

Abstract: Introduction !Pelvic Organ Prolapse (POP) is a disorder which affects millions of women worldwide [1]. POP is a condition that can negatively impact on the quality of life for patients because this condition often coexists with pelvic floor disorders like urinary or faecal incontinence [2]. If conservative treatments have failed, the surgical procedure has proven to be a good way to cure this condition with a high efficacy rate and very low rates of both mortality and morbidity [3]. The usual treatment for a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Furthermore, all patients except one were delivered in the same institute; therefore, data on the antenatal and operative records and fetal outcomes were available. Very few studies have previously reported pregnancy outcomes and recurrence risk of prolapse after laparoscopic SCP [ 2 , 7 - 9 ]. Different surgical techniques have been used in each study; three studies reported using a single mesh posterior to the cervix [ 2 , 9 , 10 ], one used anterior and posterior meshes [ 10 ], and one used a technique similar to ours, i.e., a mesh wrapped around the cervix [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, all patients except one were delivered in the same institute; therefore, data on the antenatal and operative records and fetal outcomes were available. Very few studies have previously reported pregnancy outcomes and recurrence risk of prolapse after laparoscopic SCP [ 2 , 7 - 9 ]. Different surgical techniques have been used in each study; three studies reported using a single mesh posterior to the cervix [ 2 , 9 , 10 ], one used anterior and posterior meshes [ 10 ], and one used a technique similar to ours, i.e., a mesh wrapped around the cervix [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The follow-up study was uneventful in most of the above cases except a case reported by Lewis et al, recurrence of POP after two years of delivery occurred and later managed by robotic-assisted laparoscopic supracervical hysterectomy, sacrocolpopexy, and perineorrhaphy [ 12 , 15 ]. With limited data, it is difficult to predict whether the recurrence was due to pregnancy or other underlying factors [ 16 ]. Keeping these cases in mind, all women who plan for pregnancy after surgical repair of POP should be counseled properly about the chances of recurrent prolapse and safety concerns during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Cesarean section was the preferred method of delivery among all available literature as it is logical to avoid disruption of reconstructed support [ 16 ]. Because of very limited data, it is not possible to make recommendations regarding the mode of delivery after surgery for pelvic organ prolapse [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to demographic changes, there is a growing trend of POP in women of childbearing age [ 2 ], so, many patients desire definitive surgical management prior to family completion. Many techniques have been described for the surgical treatment of POP whether vaginally, abdominally or laparoscopically exist in the literature [ 3 ], but little is published on subsequent pregnancy [ 4 ].…”
Section: Discussionmentioning
confidence: 99%